TOTP Based Authentication Using QR Code For Gateway Entry System (International Journal of Engineering and Computer Science, 2020)
In today’s scenario, there are various ways the attackers can gain access to secure information and use it for their own benefit. In this paper, we aim to improve the gateway entry system by providing more security. This system involves the use of TOTP (Time-Based One-Time Password) with QR (Quick Response) code. A QR code is a 2D matrix barcode where a large amount of information can be stored in a compact manner. TOTP is a temporary password that is active for a short duration of time. For every 30 seconds, an OTP is generated. A QR code is generated which contains the TOTP. The QR code is scanned and the server checks the TOTP generated on the server-side. If this TOTP matches with the TOTP in the QR code then the user is allowed to enter. This method increases the security of the system and prevents unauthorized access.